E-band cavity diplexer based on micromachined technology. Issue 2 (12th January 2015) - Nocella, Valeria; Pelliccia, Luca; Farinelli, Paola; Sorrentino, Roberto; Costa, Mario; Yufeng, Dai; Yanzhao, Zhou
Abstract : A robust and tuneless micromachined waveguide diplexer operating in the frequency range 71–86 GHz is here presented. The diplexer is based on multiple coupled cavities and it is manufactured using micromachining technology on two staked silicon layers. The diplexer consists of two filters combined to a common waveguide port via an E-plane T-junction. The two eight-order band-pass filters are centered at 73.5 and 83.5 GHz. The fractional bandwidths for two bands are 8.8 and 7.8% at higher- and lower-band, respectively. The measured insertion loss is below 0.7 dB for both the filters and the diplexer isolation is better than 55 dB, as required. The proposed technology allows for a very compact device (<20 × 20 × 1.5 mm) and the first prototypes were proved to be very robust to manufacturing tolerances and environmental tests, thus leading to an excellent tuneless manufacturing yield in future production. The diplexer will be employed in next generation terrestrial radio-link communications front-ends.